2021
DOI: 10.1155/2021/6675097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluations of Intraoperative Injection of Platelet‐Rich Plasma in Arthroscopic Single‐Row Rotator Cuff Repair at 2‐Year Follow‐Up

Abstract: Background. The clinical evidence is conflicted on whether platelet-rich plasma (PRP) therapies have a positive effect on tendon healing and improved functional outcomes. Purpose. To evaluate the potentials of intraoperative injection PRP on the speed and quality of healing in patients undergoing arthroscopic repair for small to medium rotator cuff tears. Methods. A total of 86 patients scheduled for arthroscopic single-row repair of small to medium rotator cuff tears were assigned to undergo either PRP inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A total of 686 patients were included, with sample sizes ranging from 42 to 102, a mean age ranging from 54 to 64 yr, and a mean follow-up ranging from 12 to 60 months. Single-row repairs were used in four studies (30,(34)(35)(36), and double-row repairs were performed for the remaining studies (29,(31)(32)(33)37,38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 686 patients were included, with sample sizes ranging from 42 to 102, a mean age ranging from 54 to 64 yr, and a mean follow-up ranging from 12 to 60 months. Single-row repairs were used in four studies (30,(34)(35)(36), and double-row repairs were performed for the remaining studies (29,(31)(32)(33)37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used leucocyte-poor PRP (29,(31)(32)(33)(35)(36)(37)(38). Four studies used platelet concentrations of approximately 5 Â 10 5 cells•μL −1 (29,30,36,37), and six studies reached platelet concentrations of approximately 10 6 cells•μL −1 (31)(32)(33)(34)(35)38). A liquid application formula was used in six studies (29,(34)(35)(36)(37)(38), whereas gel (31)(32)(33) and membrane (30) were preferred for the others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each preparation, 50 ml of blood was collected from the median cubital vein using a 50-gauge needle, ensuring that the ratio of blood to anticoagulant was 9:1. PRP was prepared using a standard collection program during the surgery as described previously [8]. The collected blood was transferred to a separation tube (Weigao New Polymer Materials Co., Ltd) and centrifuged twice: once to separate the erythrocytes and subsequently to concentrate the platelets (378 × g for 10 min each).…”
Section: Preparation Of Platelet-rich Plasmamentioning
confidence: 99%
“…Adding to the PRP controversy is a recent study by Li et al 3 that similarly found a lower retear rate at 2-year follow-up after RCR in small-and medium-sized tears augmented with PRP. Yet, they used a leukocyte-rich PRP with >6Â platelet and leukocyte concentration.…”
Section: In 2014mentioning
confidence: 99%